Characteristics of prosthetic vision in rats with subretinal flat and pillar electrode arrays. (30th October 2019) - Ho, Elton; Lei, Xin; Flores, Thomas; Lorach, Henri; Huang, Tiffany; Galambos, Ludwig; Kamins, Theodore; Harris, James; Mathieson, Keith; Palanker, Daniel
Abstract: Objective . Retinal prostheses aim to restore sight by electrically stimulating the surviving retinal neurons. In clinical trials of the current retinal implants, prosthetic visual acuity does not exceed 20/550. However, to provide meaningful restoration of central vision in patients blinded by age-related macular degeneration (AMD), prosthetic acuity should be at least 20/200, necessitating a pixel pitch of about 50 µ m or lower. With such small pixels, stimulation thresholds are high due to limited penetration of electric field into tissue. Here, we address this challenge with our latest photovoltaic arrays and evaluate their performance in vivo . Approach . We fabricated photovoltaic arrays with 55 and 40 µ m pixels (a) in flat geometry, and (b) with active electrodes on 10 µ m tall pillars. The arrays were implanted subretinally into rats with degenerate retina. Stimulation thresholds and grating acuity were evaluated using measurements of the visually evoked potentials (VEP). Main results . With 55 µ m pixels, we measured grating acuity of 48  ±  11 µ m, which matches the linear pixel pitch of the hexagonal array. This geometrically corresponds to a visual acuity of 20/192 in a human eye, matching the threshold of legal blindness in the US (20/200). With pillar electrodes, the irradiance threshold was nearly halved, and duration threshold reduced by more than three-fold, compared to flat pixels. With 40 µ m pixels, VEP was too low for reliable measurements of the grating acuity, even with pillar electrodes. Significance . While being helpful for treating a complete loss of sight, current prosthetic technologies are insufficient for addressing the leading cause of untreatable visual impairment—AMD. Subretinal photovoltaic arrays may provide sufficient visual acuity for restoration of central vision in patients blinded by AMD.